Income and Welfare Analysis of Potato Farmers in Sumberbrantas, Batu - Muhammad Auliya Rahman Natadipura; Dona Wahyuning Laily; Mirza Andrian Syah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Poverty among farmers is still present despite efforts to develop agriculture to increase farmers' income. The amount of household income influences the degree of household well-being. When household income rises, household expenditure typically increases accordingly. Consequently, higher-income households achieve greater prosperity than those with lower incomes. Sources of household income include earnings from farming activities such as cultivation, activities outside cultivation, and activities beyond the agricultural sector. The poverty rate in Batu City continues to decline because many residents have switched professions from farmers to the tourism sector. After all, farming does not provide welfare for farmers. This paper analyzes household income, assesses potato farmers' welfare, and identifies factors influencing potato farmers' welfare in Sumberbrantas Village, Bumiaji District, Batu City. The research period is March 2024—Proportionate Stratified Random Sampling method with 67 respondents. Primary data collection was done through interviews and the use of questionnaires. The first objective is analyzed by calculating on-farm, off-farm, and non-farm income. The second objective was analyzed by measuring the level of well-being using Sajogyo's theory. The third objective is analyzed using binary logit regression. The findings of this study show that the average farmer's income is relatively high, with the highest income coming from potato farming.